Surface glycoproteins determine the feature of the 2009 pandemic H1N1 virus - Kim, Jin Il (Korean Society for Biochemistry and Molecular Biology, 2012)
After the outbreak of the swine-origin influenza A H1N1 virus in April 2009, World Health Organization declared this novel H1N1 virus as the first pandemic influenza virus (2009 pH1N1) of the 21(st) century. To elucidate the characteristics of 2009 pH1N1, the growth properties of A/Korea/01/09 (K/09) was analyzed in cells. Interestingly, the maximal titer of K/09 was higher than that of a seasonal H1N1 virus isolated in Korea 2008 (S/08) though the RNP complex of K/09 was less competent than that of S/08. In addition, the NS1 protein of K/09 was determined as a weak interferon antagonist as compared to that of S/08. Thus, in order to confine genetic determinants of K/09, activities of two major surface glycoproteins were analyzed. Interestingly, K/09 possesses highly reactive NA proteins and weak HA cell-binding avidity. These findings suggest that the surface glycoproteins might be a key factor in the features of 2009 pH1N1. [BMB Reports 2012; 45(11): 653-658]